EVALUASI PENGOLAHAN LIMBAH CAIR RUMAH SAKIT DENGAN SISTIM BIO NATURAL (STUDI KASUS DI RSUD KELET JEPARA) - Aris Budi Setyawan; Eko Hartini (Dian Nuswantoro Semarang, 2012)
Background. Hospitals not only produces organic and inorganic waste, but also infectious waste containing hazardous toxic materials (B3). Wastewater Treatment Plant (WWTP)Hospital Kelet Jepara implement wastewater management Bio Natural system. After operating for more than a year has not been done evaluating whether hospitals Kelet WWTP withBio Natural system capable of treating wastewater to meet established quality standards. This study aims to evaluate the effectiveness of the WWTP with Bio Natural systems inreducing the chemical parameters in the wastewater by effluent quality standards according to the Central Java Provincial Regulation No.10 of 2004.Method. The type and design of the study was a descriptive cross sectional approach. In this case the only researchers to make observations and measurements of the levels ofBOD, COD, ammonia, phosphat parameters, without any intervention or treatment of liquid waste water treatment plant there. Where samples in this study were drawn at the WWTPinlet, after a septic tank, baffled reactors, anaerobic filters, and the pool of indicators.Result. Jepara Kelet Hospital WWTP Bio Natural systems are effective in lowering levels of 84.82% BOD, COD content of 93.04%, 94.75% Ammonia levels. Phosphate levels do notmeet quality standards, the effectiveness of only 39.21%. Efforts is to increase the flowering plant that has flowers such as the ability to absorb phosphate kana, Phragmites sp, Cyperussp, sp typa.Key Words: Bio Natural, BOD, COD, Amoniak, Phospat.